REHABILITATION OF CHILDREN WITH FUNCTIONAL (OBSTIPATIONAL) ENCOPRESIS - M.Yu. Denisov ("Paediatrician" Publishers LLC, 2010)
Author describes peculiarities of functional (obstipational) encopresis in children with prolonged chronic constipation. Disease relates to many predisposing factors; the most significant ones are perinatal pathology, disorders of nutritional behavior, psychological traumatic experience and social disadaptation of patient. Complex rehabilitation program of children with functional encopresis allows provision of optimal medical care. Key words: children, functional ecopresis, fecal incontinence, treatment.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(5):121-126)